Women Who Wear the Face Veil: Following Trends, Influenced by Studies, or Covering Their Aurat? - Hanapi, Agustin; Husnul, Muhammad; Aini, Sarina; Lubis, Asmuliadi; Solin, Siti Dian Natasya (Sharia and Law Faculty, 2023)
The Islamic perspective on the veil is bound and limited by the concept of aurat. Some scholars view the face as not part of the aurat, therefore the face does not have to be covered with a veil. Others see and conclude that the face is a woman's private parts, so it is mandatory for women to cover their faces with a veil. Cultural, social and political perspectives also follow the veil trend in society. This research aims to look at the motivation for using the veil as practiced by students at the Faculty of Sharia and Law (FSH) UIN Ar-Raniry. Next, these motivations are analyzed with a review of Islamic law and culture. The determination of locus is because FSH students are well-known (familiar) with legal matters, so the use of the veil should at least be considered based on a scientific approach. Apart from that, we want to get a detailed and detailed picture of the laws of the veil and the various responses to its use in society. There were ten female students who wore the niqab who were interviewed for several different reasons. The results obtained are related to the motivation to use the veil among students because (1) they follow along with seniors without knowing the reasons and urgency in more depth; (2) often take part in studies, because wearing the veil is understood as sunnah and is inspired by other people.